Neuroprotection: The Emerging Concept of Restorative Neural Stem Cell Biology for the Treatment of Neurodegenerative Diseases - Carletti, Barbara (Bentham Science Publishers Ltd, 2011)
During the past decades Neural Stem Cells have been considered as an alternative source of cells to replace lost neurons and NSC transplantation has been indicated as a promising treatment for neurodegenerative disorders. Nevertheless, the current understanding of NSC biology suggests that, far from being mere spare parts for cell replacement therapies, NSCs could play a key role in the pharmacology of neuroprotection and become protagonists of innovative treatments for neurodegenerative diseases. Here, we review this new emerging concept of NSC biology.